Next-generation sequencing: a follow-up of 36,913 singleton pregnancies with noninvasive prenatal testing in central China - Lu, Wan (J Assist Reprod Genet, 2020)
PURPOSE: To evaluate the noninvasive prenatal testing (NIPT) results of 36,913 cases in Jiangxi province of central China and explore its application value in prenatal screening and diagnosis. METHODS: This retrospective analysis included 36,913 singleton pregnant women who underwent NIPT because of moderate-/high-risk pregnancy or voluntary requirements between January 2017 and December 2019 in our hospital. Chromosomal abnormalities such as trisomies 21, 18, and 13 (T21, T18, T13) and sex chromosome aneuploidies (SCAs) were judged by standard Z-score analysis. Positive NIPT results were confirmed by amniocentesis and karyotyping. Pregnancy outcomes were followed up via telephone interview. RESULTS: A total of 1.01% (371/36,913) positive cases were detected by NIPT, comprising 137, 46, 31, and 157 cases of T21, T18, T13, and SCAs, respectively. A total of 116 of T21, 27 of T18, 13 of T13, and 51 of SCAs were confirmed to be true positive; all normal cases that had been followed up were verified to be true negative. The NIPT sensitivity in T21, T18, T13, and SCAs was 100.00% individually, whereas the specificity was 99.94% (36,488/36,509), 99.95% (36,579/36,598), 99.95% (36,594/36,612), and 99.72% (36,472/36,574), respectively. Furthermore, the negative predictive values of T21, T18, T13, and SCAs were all 100%, while the positive predictive values were 84.67%, 58.70%, 41.94%, and 33.33%, respectively. CONCLUSION: NIPT is highly sensitive and has a low false positive rate in testing clinically significant fetal aneuploidies of general reproductive women. However, this technique cannot substitute for amniocentesis and karyotyping, and detailed genetic counseling is also essential for the high-risk group of NIPT.